Café de especialidad: alternativa para el sector cafetalero peruano - Castro, Pilar (2004)
Although coffee is in general a commodity, in recent years a profitable market niche has been identified: that of specialty coffee. To access this market, coffee must be of the highest quality, be produced in specific geographical microclimates, have a flavour and be extracted following rigorously established standards. Peru has comparative advantages to obtain specialty coffee because it has one of the best botanical coffee varieties, adequate climatic and geographical conditions and water availability in tropical highlands. However, in order to achieve competitiveness, it is necessary to overcome limitations in terms of resources, technology, organization and management, as well as to formulate long-term strategies in which the interests of the entire productive chain are considered, from farmers to exporters, in a "win-win" relationship based on deep knowledge of the current reality of the sector and the international market.